Non-invasive quantification of lower limb mechanical alignment in flexion. (July 2014) - Russell, David; Deakin, Angela; Fogg, Quentin A.; Picard, Frederic
Abstract Objective: Non-invasive navigation techniques have recently been developed to determine mechanical femorotibial alignment (MFTA) in extension. The primary aim of this study was to evaluate the precision and accuracy of an image-free navigation system with new software designed to provide multiple kinematic measurements of the knee. The secondary aim was to test two types of strap material used to attach optical trackers to the lower limb. Methods: Seventy-two registrations were carried out on 6 intact embalmed cadaveric specimens (mean age: 77.8 ± 12 years). A validated fabric strap, bone screws and novel rubber strap were used to secure the passive tracker baseplate for four full experiments with each knee. The MFTA angle was measured under the conditions of no applied stress, valgus stress, and varus stress. These measurements were carried out at full extension and at 30°, 40°, 50° and 60° of flexion. Intraclass correlation coefficients, repeatability coefficients, and limits of agreement (LOA) were used to convey precision and agreement in measuring MFTA with respect to each of the independent variables, i.e., degree of flexion, applied coronal stress, and method of tracker fixation. Based on the current literature, a repeatability coefficient and LOA of ≤3° were deemed acceptable. Results: The mean fixed flexion for the 6 specimens was 12.8° (range: 6–20°). The mean repeatability coefficient measuring MFTA in extension with screws or fabric strapping of the baseplate was ≤2°, compared to 2.3° using rubber strapping. When flexing the knee, MFTA measurements taken using screws or fabric straps remained precise (repeatability coefficient ≤3°) throughout the tested range of flexion (12.8–60°); however, using rubber straps, the repeatability coefficient was >3° beyond 50° flexion. In general, applying a varus/valgus stress while measuring MFTA decreased precision beyond 40° flexion. Using fabric strapping, excellent repeatability (coefficient ≤2°) was observed until 40° flexion; however, beyond 50° flexion, the repeatability coefficient was >3°. As was the case with precision, agreement between the invasive and non-invasive systems was satisfactory in extension and worsened with flexion. Mean limits of agreement between the invasive and non-invasive system using fabric strapping to assess MFTA were 3° (range: 2.3–3.8°) with no stress applied and 3.9° (range: 2.8–5.2°) with varus and valgus stress. Using rubber strapping, the corresponding values were 4.4° (range: 2.8–8.5°) with no stress applied, 5.5° (range: 3.3–9.0°) with varus stress, and 5.6° (range: 3.3–11.9°) with valgus stress. Discussion: Acceptable precision and accuracy may be possible when measuring knee kinematics in early flexion using a non-invasive system; however, we do not believe passive trackers should be mounted with rubber strapping such as was used in this study. Flexing the knee appears to decrease the precision and accuracy of the system. The functions of this new software using image-free navigation technology have many potential clinical applications, including assessment of bony and soft tissue deformity, pre-operative planning, and post-operative evaluation, as well as in further pure research comparing kinematics of the normal and pathological knee.